OPTIMALISASI PERTUMBUHAN DAN HASIL EDAMAME (Glycine max L. Merril) MELALUI PEMBERIAN PUPUK NITROGEN DAN EKSTRAK TAUGE KACANG HIJAU - Rahman Rahman; Oktavianus Lumban Tobing; Setyono Setyono (Universitas Djuanda Bogor, 2019)
This study was conducted at the experiment garden of Agrotechnology Department, DjuandaUniversity, Bogor, from July to September 2018. The study was aimed at assessing the effects ofthe application of nitrogen fertilizer and mung bean sprout extract on the growth and productionof edamame (Glycine max L. Merril) plants. The experimental design used was a factorialcompletely randomized design. The first factor is the dose of N fertilizer with four levels, namelywithout N (0 kg N / ha), a half recommendation of N fertilizer (34.5 kg N / ha), one recommendationof N fertilizer (69 kg N / ha), and one and a half recommendation of N fertilizer (103.5 kg N / ha).The second factor is the concentration of mung bean sprout extract with four levels, namely withoutmung bean sprout extract (0g tauge extract / l water), a half recommendation of mung bean sproutextract (75g tauge extract/ l water), one recommendation of mung bean sprout extract (150g taugeextract / l water) and one and a half recommendation of mung bean sprout extract (225g taugeextract/ l water). The results showed that the dose of N fertilizer significantly affected the widestleaf area. The concentration of mung bean sprout extract significantly affected the number of shootsat 6 and 7 weeks after planting (MST).Keywords: edamame soybean, N fertilizer, mung bean sprout